Social determinants of drug abuse among youth in Selangor: a case study in Serendah's rehabilitation centre / Shahera Nadia Sulaiman - Sulaiman, Shahera Nadia (2019)
Drug abuse had been known as one of the social issues that is happening in Malaysia. Even when various actions and initiative had been taken by the Malaysia's Government, according to the data received from MAMPU, the number of people that abuse drug constantly increase year by year, especially those among youth. Thus, the aim of this paper is to identify the social determinants that influence drug abuse among youth in Selangor, From the literature review that had been analysed, it was found that most of the reasons why youth involved in drug abuse were due to peer's influence, family factor and neighbourhood influence. It was found out that the number of youths in Selangor that involved in drug abuse is higher compare to the other state in Malaysia. For this research study, the data was collected by distributing questionnaires to youth whose age between 19 to 39 years old that currently receiving treatment at the Serendalvs rehabilitation centre. The data were analyse using the Statistical Package of Social Science (SPSS) to come out with the results of this study. Therefore, based on the results obtained, several recommendations had been suggested and a conclusion regarding the study had been drawn.